Os clusters criativos e as transformações no território: o Porto Digital e o Bairro do Recife. - Barros, Albérico Paes Barreto (2020)
Is witnessed in the world the fast and dynamic transformations in contemporary society. Especially in its economic restructuring, the convergence of factors such as globalization, the technological development, the emergence of new media, the fragmentation of production and consumption chains, and the creativity and innovation valorization as new assets, presents itself as driving forces for a new economy capable of showing a more just and balanced socioeconomic development path, at the local and global level. Despite the abstract character of the theme and the different positions of the authors who study these concepts, this new economy - the Creative Economy - is always associated with the urban space, where economic and human relations take place. In this context, productive arrangements or creative clusters, strengthened with the process of productive restructuring, tend to cause significant changes in urban space and cultural scenarios, being supported by deep and continuous public policies. This research is motivated: 1- by the analysis of these relationships, which has paved the construction of new creativity hubs as references of culture, entrepreneurship, technology, academic training and citizenship, as witnessed by the experiences in several analyzed cases; and 2- for the analysis of the Porto Digital cluster implementation, its relationship with Bairro do Recife and its potential for territory transformation.